(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this study is to examine law enforcement against perpetrators of criminal acts of trafficking in women in the city of Makassar and to examine the obstacles faced by law enforcement officials in handling cases of trafficking in women in the city of Makassar. This research utilizes empirical research methods, namely research with an approach carried out by conducting research by collecting primary data obtained directly from the object of research through interviews. The results of the study show that law enforcement has handled and prevented criminal acts of trafficking in women through preventive and repressive means, most of which are influenced by economic factors, lack of knowledge, family problems, and relationships. In the process of law enforcement carried out by law enforcement officials face problems such as budget support. The research recommendation is the need for critical reflection in the process of enforcing the law for the realization of collective awareness. Abstrak: Tujuan penelitian ini ialah guna menelaah penegakan hukum terhadap pelaku tindak pidana perdagangan perempuan di kota makassar dan Untuk menelaah kendala yang dihadapi oleh aparat penegak hukum dalam menangani kasus perdagangan perempuan di kota makassar. Dalam penelitian ini mempergunakan metode penelitian empiris, yakni penelitian dengan pendekatan yang dilakukan dengan cara mengadakan penelitian dengan mengmpulkan data primer yang diperoleh secara langsung dari objek penelitian melalui wawancara. Hasil penelitian memperlihatkan yakni Penegakan hukum telah menangani dan mencegah tindak pidana perdagangan Pereempuan melalui preventif dan represif yang kebanyakan korbannya dipengaruhi oleh faktor ekonomi, minimnya pengetahuan, masalah keluarga, serta pergaulan. Dalam Proses penegakan hukum yang dilakukan oleh aparat penegak hukum menghadapi permasalahan seperti dukungan anggaran. Rekomendasi penelitian yaitu perlunya refleksi kritis dalam proses menegakkan hukum demi terwujudnya kesadaran kolektif.